2014
DOI: 10.1631/jzus.b1400098
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of internal mammary artery injury after blunt chest trauma: a literature review

Abstract: Abstract:The occurrence, bleeding, and treatment of internal mammary artery (IMA) injury after blunt chest trauma have not been well described in the literature. We reviewed articles published from July 1977 to February 2014 describing IMA injury after blunt chest trauma in 49 patients. There was a predominant incidence in males and on the left side. Blunt trauma to the IMA can cause anterior mediastinal hematoma, hemothorax, pseudoaneurysm, arteriovenous fistula, and extra-pleural hematoma. Of the 49 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Several studies have shown that hemorrhagic shock disturbs this balance by enhancing the differentiations of Th2 and Tc2 cells and suppressing the differentiations of Th1 and Tc1 cells, which increases the risks (Marcu et al, 2007;Miller et al, 2007;Chen et al, 2014). In the present study, resuscitation with HES and NS significantly lowered the ratios of Th1/Th2 and Tc1/Tc2.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Several studies have shown that hemorrhagic shock disturbs this balance by enhancing the differentiations of Th2 and Tc2 cells and suppressing the differentiations of Th1 and Tc1 cells, which increases the risks (Marcu et al, 2007;Miller et al, 2007;Chen et al, 2014). In the present study, resuscitation with HES and NS significantly lowered the ratios of Th1/Th2 and Tc1/Tc2.…”
Section: Discussionsupporting
confidence: 55%
“…The purpose of this study was to compare the effects of three resuscitation fluids on immune cell regulation in the early stage of hemorrhagic shock. Specifically, we evaluated the proportion of regulatory T cells (Tregs), which help maintain immune balance, and can limit inflammatory tissue damage caused by infection, autoimmunity, allogeneic immune responses, and antitumor immunity (Belkaid and Rouse, 2005;Zhao et al, 2013); we also evaluated the ratios of helper T (Th) and cytotoxic T (Tc), which can execute many crucial immune functions (Marcu et al, 2007;Zhang et al, 2008;Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Large extrapleural hematomas may pose difficulties for surgeons at thoracotomy in terms of identifying the origin of the bleeding. Multidetector CT angiography is a time-efficient method for directing and planning therapy for patients with acute bleeding (45). Thoracic arterial angiography is a diagnostic and therapeutic option, although it involves some risk of embolic material being accidentally introduced into the anterior spinal artery (41).…”
Section: Traumamentioning
confidence: 99%
“…Thoracotomy and endovascular intervention are therapeutic options for IMA injury. In a review article of 49 patients with IMA injury due to blunt chest trauma, 22 patients (45%) underwent surgery and 20 patients (41%) underwent transcatheter embolization (9). The possible mechanisms of IMA injury include a fracture of an adjacent bony structure, such as a rib, clavicle, or sternum or shearing forces acting on the vessel during extreme acceleration or deceleration (10).…”
Section: Discussionmentioning
confidence: 99%
“…In brief CT angiography is usually recommended for assessing active arterial extravasation in the presence of vascular injury. Since the presence of a mediastinal hematoma and its anatomical location suggested a vascular origin, CT can be useful for distinguishing between angiographic and surgical intervention (9,14,15). However, in patients with specific hemodynamic changes due to severely impaired left ventricular function and mechanical circulatory support, it can be difficult to optimize contrast enhancement and diagnostic imaging quality.…”
Section: Discussionmentioning
confidence: 99%